Ghost in the machine / 2 - Carman, Patrick (Skeleton creek, 2009)
Although forbidden to see each other, Ryan and Sarah continue their investigation of the mysterious happenings at the dredge by communicating through video clips, text messages, midnight meetings, and journaling. The reader may view videos on a website by using links and passwords found in the text.